Efektivitas Pijat Gulung dan Kompres Hangat dalam Meningkatkan Produksi ASI pada Ibu Pasca Persalinan - Retno Kumalasari; Suryo Ediyono (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Breast milk production plays a vital role in supporting infant growth and development, yet many postpartum mothers face challenges during the early lactation period. In Indonesia, exclusive breastfeeding coverage remains suboptimal at 52.5% (Riskesdas), with insufficient milk production being one of the contributing factors. This study aimed to evaluate the effectiveness of rolling massage and warm compress in enhancing breast milk production. A quasi-experimental design was used with intervention and control groups, each consisting of 10 purposively selected respondents. The intervention was provided once daily for three consecutive days, 15 minutes per session, and breast milk volume was measured using the pumping test method. Results showed a significant difference in mean breast milk production between the intervention group (63.1 ml) and the control group (50.3 ml). The increase in the intervention group was 24.9 ml compared to 12.1 ml in the control group. A paired sample t-test yielded a p-value of 0.000 (<0.05), confirming the effectiveness of rolling massage and warm compress in improving breast milk production. These findings suggest that incorporating simple, non-invasive techniques such as rolling massage and warm compress into maternal health programs may help promote the success of exclusive breastfeeding.